2007
DOI: 10.2214/ajr.07.2266
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-Occluded Retrograde Transvenous Obliteration of Gastric Varices: Outcomes and Complications in 49 Patients

Abstract: Balloon-occluded retrograde transvenous obliteration is an effective treatment for the obliteration of gastric varices. However, application of this procedure to severely compromised patients should be considered carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
142
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(147 citation statements)
references
References 30 publications
5
142
0
Order By: Relevance
“…Nevertheless, B-RTO is associated with two major complications: early procedure-related complications and late portal hypertensive complications. Procedure-related complications include infection, contrastinduced nephropathy, hematoma formation, pulmonary embolism due to the migration of coils or thrombi, hemolysis and pulmonary edema resulting from the use of ethanolamine oleate iopamidol (22,23). Haptoglobin is usually administered to prevent critical hemolysis, which may cause nephropathy (24,25), as in the present case.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, B-RTO is associated with two major complications: early procedure-related complications and late portal hypertensive complications. Procedure-related complications include infection, contrastinduced nephropathy, hematoma formation, pulmonary embolism due to the migration of coils or thrombi, hemolysis and pulmonary edema resulting from the use of ethanolamine oleate iopamidol (22,23). Haptoglobin is usually administered to prevent critical hemolysis, which may cause nephropathy (24,25), as in the present case.…”
Section: Discussionmentioning
confidence: 78%
“…Haptoglobin is usually administered to prevent critical hemolysis, which may cause nephropathy (24,25), as in the present case. Portal hyper-tensive complications due to reperfusion of the shunt vessel flow include the de novo occurrence or aggravation of preexisting gastroesophageal varices or portal hypertensive gastropathy, ascites or spontaneous bacterial peritonitis (22,23,26).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is highly associated with gastric fundal varices. A previous report suggested that [21] , in cases of coexisting gastric fundal varices and esophageal varices in lower esophageal segment, the extent of esophageal varices could be aggravated after imposing obliteration therapy for gastric fundal varices. In our study, there was one patient who experienced alleviation of gastric varices with aggravated para-EV and peri-EV after receiving gastroesophageal varices treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A potentially problematic long-term sequel of B-RTO is the observed development or worsening of esophageal varices in up to 50% of patients [93]. It has been shown that treatment with haptoglobin reduces the risk of hemoglobinuria after B-RTO [94,95]. A recent randomized controlled trial of 20 patients has shown that balloon-occluded endoscopic injection sclerotherapy (BO-EIS) was as effective as B-RTO and required less sclerosant in comparison with B-RTO and was safe for prophylactic treatment of highrisk gastric fundal varices [91].…”
Section: Recommendationsmentioning
confidence: 99%
“…A recent randomized controlled trial of 20 patients has shown that balloon-occluded endoscopic injection sclerotherapy (BO-EIS) was as effective as B-RTO and required less sclerosant in comparison with B-RTO and was safe for prophylactic treatment of highrisk gastric fundal varices [91]. Concomitant hepatocellular carcinoma is the most important prognostic factor after B-RTO [94,95]. It was concluded that primary prophylaxis for high-risk gastric varices would reduce the probability of bleeding and the associated mortality.…”
Section: Recommendationsmentioning
confidence: 99%